Participatory Decision-Making and Organizational Productivity: A Study of the Delta State Public Service - OKEREKA, Onofere Princewill; ALIOGO, Nwasom Rita (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The study examined the connection between participatory decision-making and organizational productivity in Delta State public service. The study specifically examined the effects of employee involvement, commitment, and consultation on organizational productivity in the public service of Delta State. Data was gathered through the survey research design, which involved 643 employees being surveyed. Out of the 643 questionnaires distributed, only 478 were retrieved and analyzed. The investigation's primary theoretical framework was value chain theory. The theory explains how organization can improve quality of decision-making and create superior value to promote organizational productivity. Statistical Package for Social Science (SPSS) version 23 was used to analyze the data using percentages, frequency, Pearson's coefficient of correlation, and linear regression. According to the study's findings, organizational productivity in Delta State public service is positively and statistically impacted by participatory decision-making, which involves employee commitment, involvement, and consultation. The study came to the conclusion that employee involvement in decision-making significantly affects organizational productivity based on these findings. Therefore, the study suggests, among other things, that the Delta State public service management should determine and set a scope and level of employee participation in decision-making. The focus here should be on collective bargaining and proper employee recognition through job enrichment in order to affect organizational commitment. Workers should be empowered to take charge of their tasks and engage in decision-making. Their working relationships and workflow will both be greatly enhanced by this.